Minimization of copper dissolution for lead-free wave soldering in surface mount technology - Arunasalam, Mageswaran (2017)
In today’s surface mount technology, developments are in progress to move towards green manufacturing by converting all leaded soldering process to lead free soldering process. This move has brought towards safer electronic manufacturing and assembly. The conversion has brought goodness for environment but challenges in manufacturing due to metallurgy and chemistry changes. The problems occurs in almost all area starting from printed circuit board assembly (PCBA) design, surface finishing, chemistry composition, temperature control and process controls. The biggest problem has caused printed circuit board (PCB) assemblies to be scrapped due to copper dissolution problem, a condition caused by longer wetting in molten solder to achieve good barrel fills causing the bottom knee of copper layer to diffuse once in contact with molten solder during the lead free wave soldering process and its rework soldering process which causes the copper layer to lose connectivity between layers. At the time of research, there was no proper method and control over the lead free wave soldering process and its rework soldering process that can maximize the solder barrel fills, minimize the copper dissolution problem and increase the cycles in rework soldering. This brought the overall aim of this research to propose a workable and practical solution to maximize solder barrel fills, minimize copper dissolution and increase the cycles in rework soldering. The work was carried out using Six Sigma methodology through define, measure, analyze, improve and control (DMAIC) approaches. Total of five factors were identified and analyzed namely the PCB finishing and copper layer construction in PCB, component terminal and led finishing, soldering flux usage and solder alloy composition, environment control with the use of Nitrogen tunneling. Resulting from analyzing the factors, a more combined controlled factors contributing to maximizing the solder barrel fills from forty to eighty percent directly improving the yields from fifty to eighty five percent, minimization of copper dissolution defect from fifteen to half percent and increasing the cycles in rework soldering from one to three by reducing the direct contact time to molten solder with optimize solder alloy composition and process control was formulated. With this improvement, an increase of sixty percentage of boards with lower copper dissolution going through the lead free wave soldering and rework soldering were obtained, another forty percent reduction of board being scrapped were also obtained with boards going through the molten solder up to triple the times.